Pulmonary Tuberculosis in a Young Pregnant Female: Challenges in Diagnosis and Management - Manogna Maddineni; Mukta Panda (Hindawi Limited, 2008)
Background. With the world becoming a global village, tuberculosis is no longer limited to endemic areas. Our case emphasizes the impact of immigration on infectious disease epidemiology and challenges associated with diagnosis and treatment in pregnancy. Case. A 21-year-old Hispanic female presented in preterm labor and was found to be hypoxic. Chest X-ray revealed a paratracheal mass which a CT scan confirmed. PPD test was positive. Bronchoalveolar lavage did not reveal acid-fast bacilli and biopsy revealed caseating granulomas. Diagnosis and treatment were challenging due to constraints in radiological investigations, lack of initial evidence of acid-fast bacilli, and toxic profile of medications. Due to her high risk, she was started on antituberculosis regimen. The diagnosis was confirmed on Day 26 when Mycobacterium tuberculosis was isolated by DNA probe. Conclusion. A high index of suspicion is required to recognize the changing face and disease spectrum of tuberculosis and initiate treatment for better outcomes.